A Review on osteoarthritis and osteoporosis: Ongoing challenges for musculoskeletal care - Nik Mohd Hatta, Nik Noor Kaussar; Che Hasan, Muhammad Kamil (IIUM Press, 2019)
Osteoarthritis and osteoporosis are two different musculoskeletal conditions which requires everyone attention. Physically inactive and increasingly obese requires a change from treating musculoskeletal conditions to a preventive approach towards promoting lifelong musculoskeletal health among older people. Accumulating data suggest that both osteoarthritis and osteoporosis are associated with an increased risk of pain, social disturbance and reduced quality of life. This review explores the management of these musculoskeletal conditions and its challenges in providing care for people living with osteoarthritis or osteoporosis. Prevention strategies and promotion of lifelong good musculoskeletal health are challenging within the society.